Peran Hakim Dalam Implementasi Konsep Restorative Justice Pada Perkara Pidana Dengan Perempuan Dan Anak Berhadapan Dengan Hukum - Roro Nur Sabila; Suwandono, Agus (Universitas Sains dan Teknologi Komputer, 2025)
As a vulnerable group, the rights of women and children when dealing with the law are often neglected. So a system is needed in criminal acts that can focus on restoring the rights of women and children in conflict with the law, namely restorative justice. This study discusses the implementation of restorative justice for children and women in conflict with the law and the role of judges in realizing the concept of restorative justice. The type of research used is the normative juridical method through library studies. The results of the study show that the realization of the concept of restorative justice in criminal cases of women in conflict with the law is through the regulation of the Chief Justice of the Republic of Indonesia Number 1 of 2024. Meanwhile, the realization of the concept of restorative justice in criminal cases with children in conflict with the law is through the diversion system regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Supreme Court Regulation Number 4 of 2014. The role of judges must be based in moral values and justice. In implementing restorative justice, judges have their own procedures, which are regulated in the regulation of the Chief Justice of the Republic of Indonesia Number 1 of 2024.